“We need to talk about what race feels like!” Using memory work to analyse the production of race and ethnicity in research encounters - kennedy-macfoy, madeleine; Nielsen, Helene Pristed (Qualitative Studies, 2012)
This article is about the production of race and ethnicity in research encounters. It is based on a type of retrospective, comparative memory work, through which we analyse, compare and contrast our respective experiences of moments when race and ethnicity have been produced during our interactions with research participants. We suggest that adding memory work to the analysis of research experiences is one way of exposing the production of race and ethnicity in research interactions, and that a comparative approach to memory work can help clarify how positionalities may not always be good predictors of processes of racialisation in research situations. We also suggest that by looking for instances in which we have felt (or been made to feel) our own ‘difference’ or ‘sameness’, power or a sense disorientation, we may contribute to destabilising the categories and categorisations, which might otherwise go unquestioned in research encounters. Our analysis makes clear how we cannot assume any fixation of where, in whom, or in which topics race or ethnicity is located. We suggest that memory work is a useful tool for learning about the production of race and ethnicity, and comparative or contrastive memory work in collaboration with other researchers differently positioned from oneself is a useful approach when engaging in ‘researching differences’.